The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/j.pain.0000000000002279
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the dorsal, but not the ventral, hippocampus relieves neuropathic pain in rodents

Abstract: Accumulating evidence suggests hippocampal impairment under the chronic pain phenotype. However, it is unknown whether neuropathic behaviors are related to dysfunction of the hippocampal circuitry. Here, we enhanced hippocampal activity by pharmacological, optogenetic, and chemogenetic techniques to determine hippocampal influence on neuropathic pain behaviors. We found that excitation of the dorsal (DH), but not the ventral (VH) hippocampus induces analgesia in 2 rodent models of neuropathic pain (SNI and SNL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 82 publications
2
29
0
Order By: Relevance
“…Indeed, the precise activation of neurons in the VTA of MOPr-eGFP/Cre mice triggered place avoidance, supporting previous results described by Tan et al (2012), Bailly et al (2020). The use of optogenetics has also been applied to the study of chronic pain, as recently reported by Wei et al (2021). In this article, the authors shed light on the implication of the dorsal (DH), but not the ventral (VH) hippocampus in the modulation of pain (Wei et al, 2021).…”
Section: µ-Opioid Receptor Knock-in Mouse Linessupporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, the precise activation of neurons in the VTA of MOPr-eGFP/Cre mice triggered place avoidance, supporting previous results described by Tan et al (2012), Bailly et al (2020). The use of optogenetics has also been applied to the study of chronic pain, as recently reported by Wei et al (2021). In this article, the authors shed light on the implication of the dorsal (DH), but not the ventral (VH) hippocampus in the modulation of pain (Wei et al, 2021).…”
Section: µ-Opioid Receptor Knock-in Mouse Linessupporting
confidence: 82%
“…The use of optogenetics has also been applied to the study of chronic pain, as recently reported by Wei et al (2021). In this article, the authors shed light on the implication of the dorsal (DH), but not the ventral (VH) hippocampus in the modulation of pain (Wei et al, 2021). More specifically, photostimulation of DH neurons for approximately 3 h was shown to relieve tactile allodynia in the spared nerve injury (SNI) neuropathic chronic pain model (Wei et al, 2021).…”
Section: µ-Opioid Receptor Knock-in Mouse Linesmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, these data suggest that input-specific effects are central to the mPFC role in pain modulation. At the same time, the role of the ventral hippocampus in pain perception also remains unclear, because in a rodent model of early stage neuropathic pain neither optogenetic nor pharmacological activation of the ventral hippocampus produced analgesic effects (Wei et al, 2021). Multiple factors may explain these differences, including the specific pain model used, the pain duration, the strength, duration and pattern of the hippocampal stimulation, and the type of neurons stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these, several experimental studies have found that direct hippocampal manipulation alters nociceptive behavior. Activation of the dorsal hippocampus reverses neuropathic pain through local excitatory and opioidergic mechanisms affecting dorsal hippocampus functional connectivity [30]. Direct injection of the local anesthetic like lidocaine to the dentate gyrus (DG) region of the hippocampus produces analgesia [31].…”
Section: Ivyspringmentioning
confidence: 99%